Peningkatan Kualitas Publikasi dan Pengembangan Karier Inspektur Penerbangan melalui Pelatihan Karya Tulis Ilmiah untuk Direktorat Navigasi Penerbangan - Dian Anggraini Purwaningtyas; Imam Sonhaji; Nawang Kalbuana; Khoirul Anam; Ego Widoro (Politeknik Penerbangan Indonesia Curug, 2023)
Capacity building that supports the career of aviation inspectors, one of which is by writing papers. The need for partners, namely the Directorate of Aviation Navigation, will increase the competence of navigation inspectors to write papers, so scientific writing training is held. This activity is carried out for 5 days with lecture and practice methods. there are 5 main materials that are the subject of discussion and 9 sub-topics and added with practice. Of the 25 participants, 95% stated that it was useful and 100% succeeded in making the manuscript and submitting the article. Further assistance is needed so that participants can conduct research or studies and publish written works in reputable journals